Love Desire Of Erik In Gaston Leroux's Novelthe Phantom Of The Opera (1911): A Psychoanalytic Approach - Wardhani, Saktiningtyas Galuh (2012)
The problem of the study is "How is love desire reflected in Gaston Leroux's novel The Phantom of the Opera?The objective of the study is to analyze Gaston Leroux's novel The Phantom of the Opera based on its structural elements and the personality of the major character based on psychoanalytic approach by Sigmund Freud. The writer uses descriptive qualitative method. In this method, the writer uses two kinds of data sources, namely primary and secondary data source. The primary data source is Gaston Leroux's novel entitles The Phantom of the Opera published in 1911. The secondary data sources are taken from literary books, internet, articles, and other data sources related to the analysis of The Phantom of the Opera. The technique of the data collection is library technique and the technique of the data analysis is descriptive technique. Based on the analysis, the writer draws some conclusions as follows: Erik's love desire is caused by his pass experiences since he was born. Because of his appearances,he is ignored by his family and people around him. His id takes part his mind and influences him to realize his desire by using some actions mostly are evil actions. Finally, after he knows that there is someone who still loves and cares with him, his id is replaced by superego and changes Erik. Human's personality and human desire is connected each other in which desire drives someone's personality in making some decisions and actions.